Cropland‐to‐Miscanthus conversion alters soil bacterial and archaeal communities influencing N‐cycle in Northern China. Issue 9 (10th July 2021) - Zhao, Chunqiao; Li, Xiaona; Yue, Yuesen; Hou, Xincun; Guo, Qiang; Song, Jinku; Li, Cui; Zhang, Weiwei; Wang, Chao; Hou, Yanhui; Fan, Ranran; Shi, Ruishuang; et al.
Abstract: Miscanthus spp. are increasingly cultivated in cropland worldwide due to their bioenergy potential and multiple ecological services. Effects of long‐term cropland‐to‐ Miscanthus conversion without N fertilizer on soil microbiome and N cycling largely remain unknown. We aimed to explore the effects of Miscanthus conversion on soil microbiome and N cycling over a 15‐year period. We analyzed diversity, composition, and abundance of bacterial and archaeal communities using 16S rRNA amplicon sequencing, and abundances of N‐cycling‐related genes using quantitative polymerase chain reaction of 0–10 cm soils collected from bare land, cropland, 10‐year Miscanthus × giganteus, and 15‐year Miscanthus sacchriflorus land in Beijing. Conversion decreased soil sand and micro‐aggregate proportion, nitrate N (NiN), available phosphorus levels, conductivity, temperature, and pH, while increasing proportion of soil clay and macro‐aggregate (MAA), soil organic C (SOC), available N (AN), exchangeable Mg 2+ (EMg 2+ ), and available potassium (AK) contents as well as microbial C/N. Consequently, diversity, composition, and abundance of soil bacterial community exhibited larger changes than those values of archaeal community after conversion. Soil AP, EMg 2+, AK, and SOC were key factors in shifting microbiome from the cropland to Miscanthus pattern. Moreover, abundances of bacterial and archaeal communities and the N fixer gene nifH increased, whereas that of the bacterial ammonia monooxygenase gene decreased. The copies of other N‐cycling‐related genes in the two Miscanthus lands seemed similar to those values of cropland. The nifH copies negatively correlated with soil NiN and positively correlated with AN, EMg 2+, ECa 2+, SOC, AK, and MAA. We conclude that changes in soil microbiome pattern induced by the variation of soil properties enhance microbial N fixation potential, maintaining stable N levels and robust N cycling with lower N leakage risk after conversion. These results should inspire farmers and governments to large‐scale use Miscanthus on marginal cropland in Northern China. Abstract : Long‐term (15 years) cropland‐to‐ Miscanthus conversion dramatically alters the soil bacterial community because of great changes in soil physical and chemical properties. Soil available phosphorus, exchangeable Mg 2+, available potassium and soil organic C were key factors in shifting microbiome from the cropland to Miscanthus pattern. Miscanthus conversion significantly decreases the copies of the bacterial ammonia monooxygenase gene but largely increases that value of the N fixation gene, which mediates robust N cycling with lower N leakage risk in the absence of N fertilizer. These results should inspire farmers and governments to large‐scale use Miscanthus on marginal cropland in Northern China.